2015
DOI: 10.1542/peds.2014-2171
|View full text |Cite
|
Sign up to set email alerts
|

Misdiagnosis and Missed Diagnoses in Foster and Adopted Children With Prenatal Alcohol Exposure

Abstract: OBJECTIVE: The purpose of this article is to assess the rate of misdiagnosis and missed diagnoses of fetal alcohol spectrum disorders (FASD) among a population of foster and adopted youth referred to a children's mental health center.METHODS: Data were collected from a sample of 547 children who underwent a comprehensive multidisciplinary diagnostic evaluation. Utilizing current diagnostic criteria, children were diagnosed, as appropriate, with fetal alcohol syndrome, partial fetal alcohol syndrome, alcoholrel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
244
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(263 citation statements)
references
References 27 publications
(33 reference statements)
4
244
0
3
Order By: Relevance
“…The main reason is that, unfortunately, many individuals with FASD are unrecognized and/or misdiagnosed (Elias, 2013;O'Connor et al, 2006). A recently conducted study reported that within their sample 87% of youths with FASD had never been previously diagnosed or had been misdiagnosed (Chasnoff et al, 2015). There are several barriers to the early recognition been found to co-occur in individuals with FASD, which likely "mask" the FASD diagnosis (Popova et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The main reason is that, unfortunately, many individuals with FASD are unrecognized and/or misdiagnosed (Elias, 2013;O'Connor et al, 2006). A recently conducted study reported that within their sample 87% of youths with FASD had never been previously diagnosed or had been misdiagnosed (Chasnoff et al, 2015). There are several barriers to the early recognition been found to co-occur in individuals with FASD, which likely "mask" the FASD diagnosis (Popova et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…20 A recent study among a population of foster and adopted youth referred to a children's mental health center reported a FASD misdiagnosis rate of 6.4% and a missed diagnoses rate of 80.1%. 21 FAS is the FASD with the most explicit diagnostic criteria, so it only represents a fraction of individuals affected by PAE. FASDs other than FAS are more challenging to diagnose, so the true FASD prevalence remains unknown and the actual impact underappreciated.…”
Section: Epidemiologymentioning
confidence: 99%
“…Any history of adoption, especially from an environment of socioeconomic impoverishment, whether domestic or international, and any history of involvement with a US child social services system can indicate a higher likelihood of having had PAE and a need for careful screening for FASD. 21,49,81 A history of involvement with child protective services related to parental substance use or to child neglect, abuse, or abandonment is a strong marker for risk, as is a history of any out-of-home or foster care placement, including kinship care. 81 Many people are not aware of the requirement for health care providers to report FASD to child protective service systems.…”
Section: The Role Of the Pediatrician And The Medical Homementioning
confidence: 99%
“…For this reason, it is never safe to drink alcohol when trying to get pregnant or during pregnancy. FASD can include a wide range of cognitive (e.g., intelligence, executive functions, shortand long-term memory, and attention), social (e.g., communication skills and gullibility), physical (e.g., reduced height and weight, and smaller head size), and adaptive impairments (e.g., decision making and problem-solving abilities) [10][11][12][13][14]. Of critical concern is the disruption of immune system development that leads to increased risk of disease and infection throughout the exposed individual's life [15], with deleterious effects of FASD presenting not only in the individual, but also on the family and in the community.…”
Section: Fetal Alcohol Spectrum Disorder (Fasd)mentioning
confidence: 99%